1992
DOI: 10.1007/bf03008299
|View full text |Cite
|
Sign up to set email alerts
|

Selective beta1 and beta2 adrenoceptor blockade on epinephrine-induced arrhythmias in halothane anaesthetized dogs

Abstract: (6,34 +--0,74 vs 8,40 +--1,13Epinephrine exerts its effects on the heart through adrenergic receptors. Myocardial beta receptors have been considered to be one of the responsible receptors mediating the catecholamine-induced arrhythmias.l"4 Propranolol, a nonselective beta antagonist, l and 1-metoprolol, a selective beta I antagonist, 2 have been shown to prevent epinephrine-induced arrhythmia during halothane anaesthesia. Recent reports 5 have described the existence of both beta 1 and beta 2 adrenoceptors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…is Several investigators have studied the dysrhythmogenicity and prevention of epinephrine-induced arrhythmias during halothane anesthesia. 12, 13 Dimich et all 2 demonstrated that esmolol prevented and suppressed arrhythmias in dogs during anesthesia with halothane, and also demonstrated that the dysrhythmogenic dose of epinephrine increased 10-fold and 30-fold above control values by administration of 150 pg.kg-~.min -1 and 200 pg-kg-l-min -1 esmolol, respectively. 12 We showed that the dysrhythmogenic dose of epinephrine increased 10-fold above the control values with an infusion of 10 pg-kgq.min -1 landiolol.…”
Section: Discussionmentioning
confidence: 97%
“…is Several investigators have studied the dysrhythmogenicity and prevention of epinephrine-induced arrhythmias during halothane anesthesia. 12, 13 Dimich et all 2 demonstrated that esmolol prevented and suppressed arrhythmias in dogs during anesthesia with halothane, and also demonstrated that the dysrhythmogenic dose of epinephrine increased 10-fold and 30-fold above control values by administration of 150 pg.kg-~.min -1 and 200 pg-kg-l-min -1 esmolol, respectively. 12 We showed that the dysrhythmogenic dose of epinephrine increased 10-fold above the control values with an infusion of 10 pg-kgq.min -1 landiolol.…”
Section: Discussionmentioning
confidence: 97%
“…Although no arrhythmias were observed following epinephrine infiltration in the present study, the worst adverse reaction to epinephrine is a life-threatening arrhythmia [2][3][4]. In addition, since it has been reported that 1 -adrenoceptors may be involved in the mechanism of epinephrine-induced arrhythmia [5], 1 -blockers could be effective for such arrhythmias [6] if they occur. Moreover, Takahashi et al [14] reported that landiolol increased the dysrhythmogenic dose of epinephrine in dogs during halothane anesthesia.…”
mentioning
confidence: 84%